Serum FSH Levels in Coasting Programmes on the hCG Day and Their Clinical Outcomes in IVF ± ICSI Cycles. (12th February 2012) - Vitthala, Srisailesh; Bouaziz, Jerome; Tozer, Amanda; Zosmer, Ariel; Al-Shawaf, Talha
Abstract : Introduction . Coasting is the most commonly used strategy in prevention of severe OHSS. Serum FSH levels measurements during coasting may aid in optimizing the duration of coasting. Objective(s) . To study live birth rates (LBRs), clinical pregnancy rates (CPRs), and optimal duration of coasting based on serum FSH levels on the hCG day. Materials and Methods. It is a retrospective study performed between 2005 and 2008 at Barts and The London Centre for Reproductive Medicine, NHS Trust, London, UK, on 349-coasted women undergoing controlled ovarian stimulation (COS) for IVF ± ICSI. The serum FSH level measurements on the hCG day during coasting programme were analysed to predict the LBR and CPR. Result(s) . LBR and CPR were significantly higher when the FSH levels on the hCG day were >2.5 IU/L (LBR: 32.5%, P = 0.045 and CPR: 36.9%, P = 0.027) compared to FSH <2.5 IU/L. The optimal FSH cut-off level for LBR and CPR is 5.6 IU/L on the hCG day. The optimal cutoff for coasting is 4 days. Conclusion(s) . Coasting may be continued as long as either serum FSH level is > 2.5 IU/L on the hCG day without compromising the LBR and CPR or to maximum of 4 days.